2022
DOI: 10.1111/jpn.13732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary protein levels on intestinal aquaporins in weaned piglets

Abstract: This study was conducted to investigate the relationship between changes in intestinal aquaporins (AQPs) in piglets fed diets with different protein levels and nutritional diarrhoea in piglets. Briefly, 96 weaned piglets were randomly divided into four groups fed diets with crude protein (CP) levels of 18%, 20%, 22% and 24%.The small intestines and colons of the weaned piglets were collected, and several experiments were conducted. In the small intestine, AQP4 protein expression was higher in weaned piglets fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Upregulation of AQP3 and AQP9 results in severe constipation by decreasing mucus secretion and faecal water content, as well as decreasing bowel peristalsis in rats (51). Multiple studies have showed that AQP-3 and AQP-9 are localized in the mucosal layer, including epithelial and goblet cells (52)(53)(54)(55). Of note, suppression of AQP3 function in the colon results in diarrhoea (52).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of AQP3 and AQP9 results in severe constipation by decreasing mucus secretion and faecal water content, as well as decreasing bowel peristalsis in rats (51). Multiple studies have showed that AQP-3 and AQP-9 are localized in the mucosal layer, including epithelial and goblet cells (52)(53)(54)(55). Of note, suppression of AQP3 function in the colon results in diarrhoea (52).…”
Section: Discussionmentioning
confidence: 99%